Fostering Primary Education Leadership Towards Effective Teacher Professional Development in Yunnan Province, China - Wen, Xiao (Pacific International Journal, 2025)
This study examined the relationship between primary education leadership practices of school administrators and the teacher professional development (TPD) initiatives implemented by the university. Specifically, it assessed leadership across four dimensions—instructional, transformational, distributed, and socio-political—and explored how these influenced various aspects of professional development, including continuous learning, collaborative practices, technology integration, and contextual responsiveness. Utilizing a descriptive-correlational research design, data were gathered from 200 primary education teachers through structured survey instruments. Results indicated that instructional leadership was the most prominently practiced, while transformational and distributed leadership showed moderate implementation. Teacher professional development was rated positively overall, with contextual influences and technology integration emerging as the strongest areas, though continuous learning showed relative weaknesses. Statistical analyses revealed no significant differences in assessments based on sex or age, but notable variations were observed by teaching experience, particularly in perceptions of instructional leadership and collaborative practices. Importantly, correlation analysis revealed significant positive relationships between leadership practices and teacher professional development, especially in the domains of instructional and socio-political leadership with technology integration and continuous learning. These findings underscore the critical role of adaptive and inclusive leadership in shaping effective professional development environments. The study concludes by proposing an Enhanced Leadership Capacity-Building Program to strengthen school leadership and ensure more relevant, sustained, and impactful teacher development efforts.